Evaluation of oral health status of children in pretreatment and after treatment for 18 month. - Ulu, Güzel; Akyildiz, M; Doğusal, GÜLÇİN; DOĞUSAL, GÜLÇIN; Keleş, S; Sönmez, I (My University, 2018)
Objective: Dental caries is an important public health issue worldwide. In developing countries preventive dentistry is not common; hence, oral and dental health problems continue to generate serious economic and social issues. The aim of this study was to assess oral health and the incidence of dental caries in systemically healthy children aged 3–14 years, provide education on oral hygiene motivation, conduct the necessary preventive and restorative procedures, and reassess caries development at the 6-, 12-, and 18-month post-treatment follow-up. Methods: Systemically healthy children aged 3–14 years who applied to the Paediatric Dentistry Clinic, Faculty of Dentistry, Adnan Menderes University (ADU) were included in the study. The subjects were evaluated for oral health status and incidence of dental caries based on surveys and clinical examination, motivation for oral hygiene with necessary training, completion of preventive and restorative treatments, and development of dental caries at the 6-, 12-, and 18-month post-treatment follow-up. Results: The study included 320 patients, aged 3–14 years (mean age 8.08±3.45 years). In children included in the study, the average decayed (d), missing (m) and filled (f) primary teeth (dmft) value was 3.81 (min–max: 0–16), decayed (D), missing (M) and filled (F) permanent teeth (DMFT) value, 1.49 (min–max: 0–6), decayed (d), missing(m) and filled(f) primary teeth surface (dmfs) value, 10.11 (min–max: 0–40), and decayed (D), missing (M) and filled (F) permanent teeth surface (DMFS) value, 2.09 (min–max: 0–12). Conclusions: For the protection and maintenance of oral and dental health in dentistry, preventive approaches should be the first concern and conservative therapeutic methods should be given priority after occurrence of any dental pathology. In addition, one-time examinations are not sufficient, and children should be examined at least twice a year. This study showed that the incidence of dental caries declined in children who underwent periodical examination and preventive dental treatment
Keywords: Preventive dental treatment; Dental caries; oral hygiene; Socioeconomic level